Starting solids early…this trial is worth peanuts. Issue 9 (September 2016) - Lyon, Corey; Iacovetto, Mathew
Abstract : N/A: Perkin MR, Logan K, Tseng A, et al. Randomized trial of introduction of allergenic foods in breast‐fed infants. N Engl J Med . 2016; 374(18):1733–1743.